Expresiones de violencia en medios virtuales en las relaciones afectivas de adolescentes en el Municipio de Chipaque, Cundinamarca (2022)
The objective of this degree project was to analyze the expressions of violence through social networks in adolescents, analyzing those predisposing factors that are linked to this phenomenon, the most common types of violence in young relationships and how they are produced.